9. Response of Visitors on the Management of Animal Conservation in Taman Rusa Park of Aceh Besar, Indonesia - Abdullah Abdullah; Fahmy Armanda (The International Journal of Tropical Veterinary and Biomedical Research, 2016)
This study was done to investigate feedback of visitors on the raise of animals as conservation effort in Taman Rusa Park located at Lamtanjong Village of Aceh Besar, Indonesia. This qualitative research was performed from December 2013 up to March 2014. Respondents were 100 visitors visited the park during the study. Visitors’ responses were recorded using structured, closed questionnaire and analyzed using Chi-square. The results showed that visitors had given positive responses on the maintenance of animals in the Taman Park.